Signs and symptoms of developmental abnormalities of the genitourinary tract - Paulo Cesar Koch Nogueira; Isabel de Pádua Paz (Elsevier, 2016)
Objective: The abnormalities of the genitourinary tract development are the leading cause of chronic kidney disease (CKD) in children. The diagnosis of this disease in Brazil is late and incomplete, which results in increased morbidity and mortality in this age group. Early diagnosis of this condition is the prerogative of generalist pediatricians, and the aim of this study was to review the clinical signs and symptoms associated with developmental abnormalities of the genitourinary tract. Data sources: Based on the description of a symbolic clinical case, the authors conducted a non-systematic review of medical literature. Data synthesis: The results suggest that the following data should be used as a warning for early diagnosis of affected children: (a) combined urinary tract abnormalities (chromosomal abnormalities; sequence of malformations [VACTERLand Prune-Belly]; and musculoskeletal, digestive tract, heart, and nervous system malformations); (b) previous history (congenital anomalies of the kidney and urinary tract [CAKUT] in the family, low birth weight, and oligoamnios); (c) clinical signs (polyuria/nocturia, urinary tract infection, systemic arterial hypertension, failure to thrive, weak urinary stream, difficulty to start urination, distended bladder, non-monosymptomatic enuresis, urinary/urge incontinence, and bowel and bladder dysfunction); and (d) pre- and postnatal ultrasonographic alterations (increased anteroposterior diameter of the renal pelvis, mainly in the third trimester of pregnancy; single kidney; hydronephrosis associated with other abnormalities; and hydronephrosis with parenchymal involvement in the post-neonatal assessment). Conclusion: The suggestions shown here can help the pediatrician to establish clinical hypotheses for the early diagnosis of developmental abnormalities of the genitourinary tract without resorting to expensive and invasive procedures. Resumo: Objetivo: As anormalidades do desenvolvimento do trato geniturinário são a principal causa de doença renal crônica (DRC) em crianças. O diagnóstico dessa doença no Brasil é formulado de maneira incompleta e tardia, o que resulta em aumento na morbi-mortalidade nessa faixa etária. O diagnóstico precoce dessa condição é prerrogativa dos pediatras generalistas e o objetivo desse trabalho foi revisar os sinais e sintomas clínicos associados às anormalidades do desenvolvimento do trato geniturinário. Fontes dos dados: A partir da descrição de um caso clínico simbólico, realizamos uma revisão não sistemática da literatura médica. Síntese dos dados: Os resultados sugerem que os seguintes dados devem ser utilizados como alerta para o diagnóstico precoce das crianças acometidas: a) anomalias do trato urinário compostas (anomalias cromossômicas, sequências de malformações - VACTERL e Prune-Belly, malformações musculoesqueléticas, do trato digestivo, cardíacas e do sistema nervoso), b) antecedentes (anomalias congênitas do rim e trato urinário (CAKUT) na família,baixo peso ao nascer e oligoâmnio), c) sinais clínicos (polaciúria/noctúria, infecção urinária, hipertensão arterial sistêmica, baixo ganho de peso, jato urinário fraco, dificuldade para iniciar a micção, bexigoma, enurese não monossintomática, urge/incontinência urinária, disfunção do intestino e da bexiga)e d) alterações ultrassonográficas ante e pós-natais (diâmetro ântero-posterior da pélvis renal aumentado principalmente no terceiro trimestre da gestação, rim único, hidronefrose associada a outras anomalias e hidronefrose com comprometimento de parênquima na avaliação pós-neonatal). Conclusão: As sugestões apresentadas podem ajudar o pediatra a estabelecer hipóteses clínicas para o diagnóstico precoce das anormalidades do desenvolvimento do trato geniturinário sem utilização de metodologias caras e invasivas. Keywords: Urinary tract malformations, Chronic kidney disease, Early diagnosis, Child, Palavras-chave: Malformação do trato urinário, Doença renal crônica, Diagnóstico precoce, Criança